Radiologist-patient interactions: implications for picture archiving and communications systems and teleradiology...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Williamson EE; Williamson B Jr. (Journal of Digital Imaging)
We analyzed radiologist-patient interactions and found that radiologic examinations can be classified into three categories: those involving direct interaction of the radiologist with each patient, those involving interaction of the radiologist with some of the patients, and those that do not involve interaction between the radiologist and the patient. We then analyzed the staff assignments of a large academic radiology practice and a moderate-sized radiology department. Both departments include a full range of inpatient and outpatient procedures. We concluded that about 50% of the radiologists in these practices could interpret examinations at a location independent of the site where the examination was performed. This type of analysis can be helpful in planning for the reengineering of radiology processes following implementation of picture archiving and communications systems (PACS) and teleradiology. Copyright (c) 1999 by W.B. Saunders Company